Learning mathematics using an ethnomathematics approach: a systematic literature review - Hendriyanto, Agus; Priatna, Nanang; Juandi, Dadang; Dahlan, Jarnawi Afgani; Hidayat, Riyan; Sahara, Sani; Muhaimin, Lukman Hakim (North American Business Press, 2023)
The study of ethnomathematics has grown significantly over the decades, especially for teaching academic mathematics in schools. However, only a small number of studies comprehensively examine research trends in the use of ethnomathematics for mathematics learning. Thus, research trends for the years 2018 to 2022 were thoroughly analyzed through systematic literature reviews referring to the standards of Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA). This review found 24 journal articles from the top indexing databases called Scopus and Eric. The finding of the SLR indicate that two types of ethnomathematics research are found if categorized based on the research data source. The ‘cultural forms’ used in ethnomathematics research into three categories: ideas, activities, and artifacts. Indonesian researchers (n=19) dominated the collected studies as systematic review only included publications published in English. The categorization of the studies are ethnomathematics (pure) and ethno-modelling, and the most studied mathematical topics are geometry (n=11), followed by algebra (n=5), numbers (3), sets (n=2), and arithmetic (n=1).